Fenugreek derived diosgenin as an emerging source for diabetic therapy - Tak, Yamini; Kaur, Manpreet; Chitranashi, Abhishek; Samota, Mahesh Kumar; Verma, Preeti; Bali, Manoj; Kumawat, Chiranjeev (Frontiers in Nutrition, 2024)
Diabetes is a chronic metabolic disease that endangers the entire body's tissues and organs.Diabetes impairs glucose and insulin regulation in the human body by causing pancreatic cell damage. Diabetes modifies pathways such as serine/threonine protein kinase (Akt) and Protein kinase C (PKC)/-glucose transporter 4 (GLUT4), peroxisome proliferator-activated receptor (PPAR) glucose absorption, and inhibits α-amylase and α-glucosidase, Sodium/glucose cotransporter 1 (SGLT-1), and Na + -K + -ATPase activity. Diabetes may also be caused by a decrease in the expression of sterol regulatory element binding protein 1 (SREBP-1) and its target genes, fatty acid synthase (FAS), stearoyl-CoA desaturase-1 (SCD-1), and acetyl-CoA carboxylase α (ACC), as well as a decrease in the levels of C/EBP homologous protein (CHOP), Caspase12, and Caspase3 proteins. Diabetes has long been linked to diseases of the cardiovascular, nervous, skeletal, reproductive, hepatic, ocular, and renal systems. Diosgenin, a steroidal compound derived from fenugreek, aids in the prevention of diabetes by altering cellular pathways in favor of healthy bodily functions. Diosgenin is a new nutraceutical on the market that claims to cure diabetes in particular. This article focuses on diosgenin extraction and purification, fenugreek bioactive compounds, pharmacological properties of diosgenin, mode of action of diosgenin to cure diabetes, and dosages.